CLINICO – MICROBIOLOGICAL AND THERAPEUTIC STUDIES ON CANINE OTITIS EXTERNA** - K. LAKSHMI; D. S. TIRUMALA RAO (International Journal of Pharma and Bio Sciences, 2013)
The study was conducted on 48 clinical cases of dogs with the objective of recording clinical signs, identifying etiological agents and therapeutic management of otitis in dogs. Various clinical signs of otitis were aural pruritus , ear pain, foul odour of ear discharge, head tilt, erythema of pinna, alopacia ,scaling, crusting of pinna and swelling at the base of the ear canal. Otoscopic examination of the affected ear of 48 dogs revealed erythema of ear canal, and exudates that were yellowish purulent, brownish and black thick discharge. The result of the cultural examination of discharges revealed growth of bacteria viz Staphylococcus aureus Streptococcus spp, Pseudomonas aeruginosa, E.coli and Proteus spp . Apart from bacteria, fungal isolates like Aspergillus spp and Malassezia pachydermatitis yeast were identified. The antibiotic sensitivity test showed highest sensitivity towards Ciprofloxacin. The invitro disc diffusion test using antifungal discs showed the highest sensitivity towards Ketoconazole. The therapeutic response in treating otitis with Ciprofloxacin topical and oral was more effective than ofloxacin topical and oral preparations. Similarly, a combination of Ketoconazole orally & Ciprofloxacin topically was more effective than the combination of Clotrimazole topically and Ofloxacin orally.